Lead poisoning in children from townships in the vicinity of a lead–zinc mine in Kabwe, Zambia. (January 2015) - Yabe, John; Nakayama, Shouta M.M.; Ikenaka, Yoshinori; Yohannes, Yared B.; Bortey-Sam, Nesta; Oroszlany, Balazs; Muzandu, Kaampwe; Choongo, Kennedy; Kabalo, Abel Nketani; Ntapisha, John; Mweene, Aaron; Umemura, Takashi; et al.
Highlights: We measured blood lead levels in children near a Pb–Zn mine in Zambia. 100% of the sampled children under 7 years had BLLs > 5 μg dL −1 . Highest BLLs were seen in children around the age of 2 years. BLLs > 150 μg dL −1 were recorded 8 children with a maximum of 427.8 μg dL −1 . The children living around the Pb–Zn mine are at serious risks of Pb poisoning. Abstract: Childhood lead poisoning is a serious public health concern worldwide. Blood lead levels exceeding 5 μg dL −1 are considered elevated. In Kabwe, the capital of Zambia's Central Province, extensive Pb contamination of township soils in the vicinity of a Pb–Zn mine and posing serious health risk to children has been reported. We investigated BLLs in children under the age of 7 years in townships around the mine; where blood samples were collected and analyzed using an ICP-MS. All of the sampled children had BLLs exceeding 5 μg dL −1 . Children in these areas could be at serious risk of Pb toxicity as 18% of the sampled children in Chowa, 57% (Kasanda) and 25% (Makululu) had BLLs exceeding 65 μg dL −1 . Eight children had BLLs exceeding 150 μg dL −1 with the maximum being 427.8 μg dL −1 . We recommend that medical intervention be commenced in the children with BLL exceeding 45 μg dL −1 .